ChemInform Abstract: Asymmetric Synthesis of CP‐99, 994 by Ring‐Expanding Amination of Monosubstituted Prolinols. Issue 28 (June 2016) - Yamagiwa, Noriyuki; Watanuki, Sayaka; Nishina, Takahiro; Suto, Yutaka; Iwasaki, Genji
Abstract: The key step of the title synthesis is a ring‐expansion rearrangement, in which the threo‐fused monosubstituted prolinol (I) is efficiently transformed to the 2, 3‐disubstituted piperidine (III) with cis‐configuration and without loss of enantiomeric purity.